2012
DOI: 10.1088/0004-637x/755/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Reverberation Mapping Results for Five Seyfert 1 Galaxies

Abstract: We present the results from a detailed analysis of photometric and spectrophotometric data on five Seyfert 1 galaxies observed as a part of a recent reverberation mapping program. The data were collected at several observatories over a 140-day span beginning in 2010 August and ending in 2011 January. We obtained high sampling-rate light curves for Mrk 335, Mrk 1501, 3C 120, Mrk 6, and PG 2130+099, from which we have measured the time lag between variations in the 5100Å continuum and the Hβ broad emission line.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
212
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(237 citation statements)
references
References 63 publications
(85 reference statements)
22
212
2
Order By: Relevance
“…Through the modeling of the AGN light curves as a damped random walk (DRW; Zu et al 2011, 2013 andreference therein), this method appears to be consistent with previous crosscorrelation techniques (e.g. Grier et al 2012, for spectroscopic reverberation data). Using the SPEAR code 2 on our light curves, we obtain a time delay of τ spear = 18.4 +1.2 −1.0 .…”
Section: B-band R-bandsupporting
confidence: 66%
See 1 more Smart Citation
“…Through the modeling of the AGN light curves as a damped random walk (DRW; Zu et al 2011, 2013 andreference therein), this method appears to be consistent with previous crosscorrelation techniques (e.g. Grier et al 2012, for spectroscopic reverberation data). Using the SPEAR code 2 on our light curves, we obtain a time delay of τ spear = 18.4 +1.2 −1.0 .…”
Section: B-band R-bandsupporting
confidence: 66%
“…Because the narrow-band collects both the emission line flux and the underlying continuum, the challenge is to extract the pure emission line light curve. In the dedicated case study of 3C 120, Pozo Nuñez et al (2012) demonstrated that PRM reaches an accuracy similar to spectroscopic RM (Grier et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Because the iron line has the main advantage of being in a 'clean' part of the spectrum, where it is not affected by the reprocessed black body emission or by continuum luminosity and broad line region radius, which can be used to estimate black hole mass when combined with optical line width (e.g. Kaspi et al 2000;Grier et al 2012), or the correlation between black hole mass and host galaxy bulge stellar velocity dispersion (e.g. Gebhardt et al 2000).…”
Section: The Iron K Lagmentioning
confidence: 99%
“…Such work has culminated in the measurement of black hole masses for a wide range of AGN (e.g. Grier et al 2012 and see Peterson & Bentz 2006 for a review) and is now leading to the measurement of the detailed structure of the BLR, identifying its inclination to the observer as well as whether the gas is simply orbiting, outflowing, inflowing or some combination of all three (Bentz et al 2010;Pancoast et al 2011Pancoast et al , 2013Grier et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Notable early attempts include Wanders et al (1995), Done & Krolik (1996), and Ulrich & Horne (1996), but recovered maps of velocity-resolved results, reminiscent of those shown in Figure 5, were ambiguous at best. In the last few years, however, reverberation programs have enjoyed much more success given the careful experimental setup and the resultant high quality of the data (Bentz et al 2009b(Bentz et al , 2010aDenney et al 2010;Grier et al 2012;De Rosa et al 2015).…”
Section: Blr Geometry and Kinematicsmentioning
confidence: 99%